PENGARUH ADOPSI ARTIFICIAL INTELLIGENCE DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2021-2024 - Shira Amanda Putri; Salma Taqwa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: How well a company reports its finances depends a lot on the estimates and accounting method choices that management makes, like the way they handle discretionary accrual. Because this part is related to legal accounting rules, how it is used depends entirely on the management's personal choices when sharing financial information. Aiming to gather empirical insights, this study analyzes the impact of artificial intelligence adoption and internal controls on financial reporting quality. The study covers conventional banking companies listed on the Indonesia Stock Exchange (IDX) over four years (2021–2024).Methods: This study employed a quantitative research design utilizing secondary data sourced from annual reports. A total of 108 companies were sampled based on specific criteria using a purposive sampling approach. To evaluate the data, multiple linear regression modeling was performed using SPSS 25.Results: The findings indicate that AI adoption is associated with a significant decline in financial reporting quality. Although internal control does not individually impact financial reporting quality, simultaneous testing confirms that the combined effect of AI adoption and internal control significantly influences the quality of financial reporting. Conclusion: In the banking sector, AI adoption alone may not guarantee high-quality financial reporting, while the contribution of internal control remains limited. Therefore, banking institutions, regulators, and stakeholders should strengthen AI governance to support reliable financial reporting. Keywords: Artificial Intelligence, Banking, Financial Reporting Quality, Internal Control